Does the combination of optimal substitutions at the C2-, N5- and N8-positions of the pyrazolo-triazolo-pyrimidine scaffold guarantee selective modulation of the human A3 adenosine receptors? - Cheong, S.; Dolzhenko, Anton; Paoletta, S.; Lee, E.; Kachler, S.; Federico, S.; Klotz, K.; Dolzhenko, A.; Spalluto, G.; Moro, S.; Pastorin, G. (Elsevier, 2011)
In an attempt to study the optimal combination of a phenyl ring at the C2-position and different substituents at the N5- and N8-positions towards the selective modulation of human A3 adenosine receptors (hA3AR), we synthesized a new series of 2-para-(un)substituted-phenyl-pyrazolo-triazolo-pyrimidines bearing either a methyl or phenylethyl at N8 and chains of variable length at N5. Through biological evaluation, it was found that the majority of the compounds had good affinities towards the hA3AR in the low nanomolar range. Compound 16 possessed the best hA3AR affinity and selectivity profile (KihA3 = 1.33 nM; hA1/hA3 = 4880; hA2A/hA3 = 1100) in the present series of 2-(substituted)phenylpyrazolo-triazolo-pyrimidine derivatives. In addition to pharmacological characterization, a molecular modeling investigation on these compounds further elucidated the effect of different substituents at the pyrazolo-triazolo-pyrimidine scaffold on affinity and selectivity to hA3AR.